Agresivitas Pajak Perusahaan Melalui Related Party Transaction, Hutang Dan Aset Tetap - Nico Alexander; Muhammad Dimas Indrawan (JURNAL AKUNTANSI DAN AUDIT TRI BHAKTI, 2023)
Corporate aggressiveness is the company's attempt to reduce corporate taxes. There are many method that companies do, but in this study using 3 method, namely related party transactions, debt and fixed assets. Therefore this study aims to obtain empirical evidence regarding the effect of related party transactions, debt and fixed assets on the aggressiveness of companies to reduce their taxes. The objects used in this study were manufacturing companies listed on the Indonesia Stock Exchange (IDX) from 2019 to 2021. 60 manufacturing companies were selected as research samples using purposive sampling. This study uses multiple regression to test the hypothesis. The results showed that the level of debt has a positive effect on tax aggressiveness which indicates that companies that have high debt values will reduce aggressiveness towards corporate taxation. This is because companies that have a large debt value will have a large interest rate as a deduction from corporate tax, so that the tendency of companies to take actions that can reduce taxes will also decrease. The results of this study provide information to tax regulators regarding thefactors that influence companies to carry out tax aggression, so that tax regulators can adjust existing regulations so that tax revenues remain on target.